2018
DOI: 10.1021/acs.langmuir.8b01100
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrostatic Pressure on the Corrosion Behavior of Superhydrophobic Surfaces on Bare and Oxidized Aluminum Substrates

Abstract: It is generally recognized that superhydrophobic surfaces in water may be used for corrosion resistance due to the entrapped air in the solid/liquid interface and could find potential applications in the protection of ship hull. For a superhydrophobic surface, as its immersion depth into water increases, the resultant hydrostatic pressure is also increased, and the entrapped air can be squeezed out much more easily. It is therefore predicted that high hydrostatic pressure would cause an unexpected decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 22 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…The anticorrosion capability of micro‐/nanostructured surface can be attributed to the entrapped air pocket between corrosive liquid and rough surface, which can be illustrated by the Cassie superhydrophobic state. The protective air layer can effectively block the diffusion of corrosive species, such as Cl − ( Figure a) . Besides surface micro‐/nanostructure, lowering of surface energy is also required.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anticorrosion capability of micro‐/nanostructured surface can be attributed to the entrapped air pocket between corrosive liquid and rough surface, which can be illustrated by the Cassie superhydrophobic state. The protective air layer can effectively block the diffusion of corrosive species, such as Cl − ( Figure a) . Besides surface micro‐/nanostructure, lowering of surface energy is also required.…”
Section: Applicationsmentioning
confidence: 99%
“…a) Schematic illustration showing the anticorrosion mechanism of superhydrophobic surfaces . Copyright 2018, American Chemical Society.…”
Section: Applicationsmentioning
confidence: 99%
“…Ou et al used superhydrophobic aluminium samples immersed at varying depths in aqueous NaCl to observe the corrosion behaviour. 130 The results indicated that, as hydrostatic pressure increased, the degradation of superhydrophobicity increased and more severe corrosion was observed for nonoxidised samples. The air layer acting as a protective barrier was lost at increased pressures allowing corrosive species, such as Cl À ions, to reach the surface.…”
Section: Pressurementioning
confidence: 96%
“…Fig.18Schematic of the oxygen corrosion of the aluminium substrate and proposed corrosion mechanism. Reproduced with permission from ref 130…”
mentioning
confidence: 99%
“…Al alloys have been extensively used as engineering components, parts and plates in shipbuilding and oceanic engineering areas because of their easy accessibility, good workability, high specific strength and low price [1,2]. Usually, Al alloys are easily oxidized to protect themselves from corrosion [3]. However, reactive anions can erode metallic substrates thereby leading to corrosion failures in wet conditions [4].…”
Section: Introductionmentioning
confidence: 99%